ChemInform Abstract: Diverted Total Synthesis of Falcitidin Acyl Tetrapeptides as New Antimalarial Leads. Issue 34 (26th August 2014) - Kotturi, Santosh R.; Somanadhan, Brinda; Ch'ng, Jun‐Hong; Tan, Kevin S.‐W.; Butler, Mark S.; Lear, Martin J.
Abstract The total syntheses of antimalarial agent Falcitidin (I) as well as related N‐acyl analogues (II) are outlined and the efficiency of the latter compounds against chloroquine‐sensitive Plasmodium falciparum 3D7 is tested.